Childhood injury prevention practices by parents in Mexico. Issue 4 (1st December 2002) - Mock, C; Arreola Rissa, C; Trevino Perez, R; Almazan Saavedra, V; Enrique Zozaya, J; Gonzalez Solis, R; Simpson, K; Hernandez Torre, M
Abstract : Objective: Scientifically based injury prevention efforts have not been widely implemented in Latin America. This study was undertaken to evaluate the baseline knowledge and practices of childhood safety on the part of parents in Monterrey, Mexico and in so doing provide information on which to base subsequent injury prevention efforts. Methods: Interviews were carried out with parents from three socioeconomic strata (upper, middle, lower). Questionnaires were based on Spanish language materials developed by The Injury Prevention Program (TIPP) of the American Academy of Pediatrics. Results: Data were obtained from parents of 1123 children. Overall safety scores (percent safe responses) increased with increasing socioeconomic status. The differences among the socioeconomic groups were most pronounced for transportation and less pronounced for household and recreational safety. The differences were most notable for activities that required a safety related device such as a car seat, seat belt, helmet, or smoke detector. Appropriate use of such devices declined from 47% (upper socioeconomic group) to 25% (middle) to 15% (lower). Conclusions: Considerable differences in the knowledge and especially the practice of childhood safety exist among parents in different socioeconomic levels in Mexico. Future injury prevention efforts need to address these and especially the availability, cost, and utilization of specific highly effective safety devices.